Nilai-Nilai Kearifan Lokal Dalam Kumpulan Cerita Rakyat Nusantara - Halimah Halimah; Ida Komalasari (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Values of Local Wisdom in the Collection of Nusantara Folklore This study is motivated by the importance of preserving Indonesian cultural values embedded in folklore as a form of inherited heritage. Folklore serves not only as entertainment but also as an educational medium containing moral messages and local wisdom. However, in the era of globalization, these values are at risk of fading if not systematically studied and documented. Therefore, this study aims to describe the values of local wisdom in terms of peace and welfare aspects found in the book Kumpulan Cerita Rakyat Nusantara, based on a literary anthropology perspective using Robert Sibarani’s concept. This research employs a descriptive qualitative approach with a library research design. The primary data source is the text of folklore contained in the book, while secondary data are obtained from relevant literature. Data collection techniques include documentation and in-depth reading (close reading). Data analysis is conducted using content analysis through data reduction, data display, and conclusion drawing. Data validity is ensured through source and theoretical triangulation. The results reveal that there are 198 instances of local wisdom categorized into two main aspects: peace (122 data) and welfare (76 data). The peace aspect includes values such as politeness, honesty, harmony, gratitude, and social solidarity. Meanwhile, the welfare aspect consists of hard work, cooperation, discipline, and cultural preservation. These findings indicate that Indonesian folklore plays a significant role in character building and the preservation of cultural values, making it highly relevant as instructional material in education based on local wisdom.